Mesoscale atmosphere ocean coupling enhances the transfer of wind energy into the ocean - Byrne, David; Münnich, Matthias; id_orcid:0 000-0003-3292-2934; Frenger, Ivy; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310 (Nature, 2016)
Although it is well established that the large-scale wind drives much of the world’s ocean circulation, the contribution of the wind energy input at mesoscales (10–200 km) remains poorly known. Here we use regional simulations with a coupled high-resolution atmosphere–ocean model of the South Atlantic, to show that mesoscale ocean features and, in particular, eddies can be energized by their thermodynamic interactions with the atmosphere. Owing to their sea-surface temperature anomalies affecting the wind field above them, the oceanic eddies in the presence of a large-scale wind gradient provide a mesoscale conduit for the transfer of energy into the ocean. Our simulations show that this pathway is responsible for up to 10% of the kinetic energy of the oceanic mesoscale eddy field in the South Atlantic. The conditions for this pathway to inject energy directly into the mesoscale prevail over much of the Southern Ocean north of the Polar Front. ISSN:2041-1723